2020
DOI: 10.1101/2020.09.05.284133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population receptive fields in non-human primates from whole-brain fMRI and large-scale neurophysiology in visual cortex

Abstract: Population receptive field (pRF) modeling is a popular method to map the retinotopic organization of the human brain with fMRI. While BOLD-based pRF-maps are qualitatively similar to invasively recorded single-cell receptive fields in animals, it remains unclear what neuronal signal they truly represent. We address this question with whole-brain fMRI and large-scale neurophysiological recordings in awake non-human primates. Several pRF-models were independently fit to the BOLD signal, multi-unit spiking activi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 201 publications
(423 reference statements)
0
3
0
Order By: Relevance
“…Previous studies employing electrophysiological recordings in humans and animals have shown specific neural correlates of pRF suppression and compression ( 30 , 40 , 41 ). Hence, it seems to us at least plausible that the modulatory action of activation and normalization constants could reflect not only a computational, but also a biological, property of brain responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies employing electrophysiological recordings in humans and animals have shown specific neural correlates of pRF suppression and compression ( 30 , 40 , 41 ). Hence, it seems to us at least plausible that the modulatory action of activation and normalization constants could reflect not only a computational, but also a biological, property of brain responses.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory stimulation leads to reliable positive and negative fMRI BOLD responses (PBRs and NBRs) during topographical mapping (Allison et al, 2000;Fracasso et al, 2018;Harel et al, 2002;Klink et al, 2020). NBRs can occur next to PBRs in the visual cortex and have been shown to correlate with electrophysiologically-measured neuronal inhibition (Huang et al, 1996;Shmuel et al, 2006Shmuel et al, , 2002.…”
Section: Suppressed or Negative Imaging Signalsmentioning
confidence: 99%
“…These processes frequently encompass regions in the visual field (VF) spanning distances bigger than pRF sizes in V1. Thus, perceptual organization needs information integration across sizeable visual field sectors, usually thought to be achieved in higher-order visual areas with larger RFs (Klink et al, 2021; Wandell & Winawer, 2015).…”
Section: Introductionmentioning
confidence: 99%